2016
DOI: 10.1590/1809-4430-eng.agric.v36n6p962-971/2016
|View full text |Cite
|
Sign up to set email alerts
|

Spacial Illuminances Variability and Energy Consumption in Aviaries for Laying Hens Equiped With Compact Fluorescent Lamps and Light Emitting Diode

Abstract: ABSTRACT:The spatial illuminance distribution interferes in the commercial production of eggs and electric energy consumption, being considered the second major source of costs in the production chain. Therefore, in this study the objective was to evaluate the spatial distribution of the illuminance level and electric energy consumption in two commercial aviaries for egg production. The first aviary was equipped with compact fluorescent lamps (CFL) and the second, with light-emitting diode (LED) lamps. The ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The use of natural lighting, despite its variation during the day, promotes lower consumption of electricity, and it is up to the producer to perform the management of closing and opening of the side curtains to adapt the illuminance inside the aviary. Ribeiro et al (2016) observed lux values higher than 100, even with artificial lighting in the southern region of Minas Gerais, Brazil. Another possible alternative would be the use of a device that reduces the intensity of the electrical current of the lighting system (dimmer), which would enable the control of illuminance within the recommended range from 5 to 20 lux (Santana et al, 2014).…”
Section: Resultsmentioning
confidence: 77%
“…The use of natural lighting, despite its variation during the day, promotes lower consumption of electricity, and it is up to the producer to perform the management of closing and opening of the side curtains to adapt the illuminance inside the aviary. Ribeiro et al (2016) observed lux values higher than 100, even with artificial lighting in the southern region of Minas Gerais, Brazil. Another possible alternative would be the use of a device that reduces the intensity of the electrical current of the lighting system (dimmer), which would enable the control of illuminance within the recommended range from 5 to 20 lux (Santana et al, 2014).…”
Section: Resultsmentioning
confidence: 77%
“…where h is the distance between the samples, C 0 is the nugget effect, and a is the interval. The fitted model differs from what has been reported in the relevant literature, specifically, vis-à-vis, research that studied environmental variables in animal facilities that was fitted to the spherical model [14,[29][30][31]. The difference may be due to the sampling grid used in those studies, as well as the environmental effects and/or the experimental design.…”
Section: Data Partition Methods For Validation Of the Modelsmentioning
confidence: 75%
“…The mathematical model used to perform the semivariogram fitting was spherical, which is widely used in geostatistical studies, since they are referenced in geostatistics as transitive models (models with sill C 0 + C 1 ). The selection of the spherical model is justified because it is the one that best adapted to the fits in studies in the environmental variables in facilities for animals (Ponciano et al, 2013;Gonçalves et al, 2016;Ribeiro et al, 2016). From the fit of a mathematical model to the calculated values of γ (h), the following coefficients of the theoretical model for the semivariogram are calculated: nugget effect (C 0 ), sill (C 0 + C 1 ) and range (a).…”
Section: Resultsmentioning
confidence: 99%